2009
DOI: 10.1128/jvi.00925-09
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 V1-to-V5 Envelope Variants from the Chronic Phase of Infection Use CCR5 and Fuse More Efficiently than Those from Early after Infection

Abstract: Human immunodeficiency virus type 1 (HIV-1) envelope glycoprotein modifications over the course of infection have been associated with coreceptor switching and antibody neutralization resistance, but the effect of the changes on replication and host cell receptor usage remains unclear. To examine this question, unique early-and chronic-stage infection envelope V1-toV5 (V1-V5) segments from eight HIV-1 subtype A-infected subjects were incorporated into an isogenic background to construct replication-competent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
49
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 86 publications
5
49
2
Order By: Relevance
“…Indeed, when previously described cloned Envs (BBB, NNB, NBB) were tested in a replication-competent green fluorescent protein (GFP) reporter system for entry into the cell lines used in this study, the infectivities were consistent with the prior report (data not shown) (19). Using V1-V5 chimeric replication-competent subtype A viruses, Etemad et al (5) observed reduced replication in JC-10 cells for those chimeras containing the acute virus fragment relative to that for those containing fragments from chronically infected partners, although both replicated on these cells less efficiently than on JC-53 cells. Thus, it is possible that viruses from subtype A transmission pairs differ in their CCR5 requirements from those we have observed for subtype C Envs.…”
supporting
confidence: 86%
“…Indeed, when previously described cloned Envs (BBB, NNB, NBB) were tested in a replication-competent green fluorescent protein (GFP) reporter system for entry into the cell lines used in this study, the infectivities were consistent with the prior report (data not shown) (19). Using V1-V5 chimeric replication-competent subtype A viruses, Etemad et al (5) observed reduced replication in JC-10 cells for those chimeras containing the acute virus fragment relative to that for those containing fragments from chronically infected partners, although both replicated on these cells less efficiently than on JC-53 cells. Thus, it is possible that viruses from subtype A transmission pairs differ in their CCR5 requirements from those we have observed for subtype C Envs.…”
supporting
confidence: 86%
“…HIV-1 variants encoding Envs with shorter and less glycosylated variable domains were selected for during transmission, suggesting that compact Envs confer a greater transmissibility or fitness advantage in establishing new infection. Until recently, no clear functional phenotype could be attributed to the founder Env (24,34,40,(52)(53)(54). In fact, the only phenotype reported for compact Envs was increased sensitivity to neutralizing antibodies in linked donor plasma, which does not explain the selective advantage in a new host where no HIV-1 immune response has developed.…”
Section: Discussionmentioning
confidence: 99%
“…Some variable domains that are functional in the context of a particular Env backbone might not be functional in another (22). Several studies have highlighted a possible connection between the V1/V2 domain and HIV-1 infection efficiency (23)(24)(25)(26). Virions encoding chimeric BaL Env with V1/V2 domains from JR-CSF or NL4-3 replicate less efficiently in macrophages but not in lymphocyte cultures (23,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that alterations in gp120-CD4 interactions can impact viral infectivity and membrane fusion (8,22,31,32). To investigate whether reductions in ibalizumab susceptibility affect these Env-mediated functions, we assessed the in vitro infectivities of paired day 0 and week 9 virus isolates by comparing reporter gene expression levels in the HIV-1 entry assay.…”
Section: Vol 85 2011 Ibalizumab Susceptibility Of Hiv-1 3873mentioning
confidence: 99%